Tantangan dan Harapan Permainan Tradisional Di Nagari Sibakur Dalam Arus Modernisasi - Ali Basrah Pulungan; Adilla Maiwahyu Putri; Muhammad Gazi Al Ghifari; Shalma Fadilla; Selma Sri Junita (CV. ITTC INDONESIA, 2025)
This study explores the challenges and aspirations of preserving traditional games in Nagari Sibakur, Indonesia, in the face of modernization and digitalization. The study was conducted through direct observation by 29 university students over a month in three hamlets in Nagari Sibakur. The findings indicate that children and adolescents' interest in traditional games has declined due to the influence of technology and contemporary lifestyles, resulting in the games being forgotten and neglected. This creates a generational gap, where the values of togetherness, mutual cooperation, and local wisdom inherent in traditional games are slowly being lost. However, efforts to reintroduce traditional games to children and use a fun approach can increase their interest, suggesting the possibility of rejuvenating this cultural heritage. Preserving traditional games requires strategic actions such as integrating them into the school curriculum, holding competitions, and empowering communities, as well as involving the active participation of all parties, including students, the community, and the government. With this collaboration, it is hoped that traditional games will not only survive but also thrive as part of a modern local cultural identity while remaining connected to their historical roots.